Abusive Relationship Terhadap Perempuan Dalam Rumah Tangga Di Channel Youtube Rachel Vennya (Pendekatan Analisis Wacana Model Sara Mills) - Zaimatul Millah (STAI Bumi Silampari, 2021)
Violence against women in household circles committed by husbands to wives is still a frequent phenomenon in Indonesia. Through social media, especially YouTube, Rachel Vennya voiced the voice of her best friend, Adelita Morskha, on her YouTube channel, who was a victim of an abusive relationship using the Sara Mills Model Critical Discourse Analysis. The results showed that the role of women as story subjects who presented themselves in the video. However, it is also the object of storytelling, that women as victims of abuse, oppressed figures, weak people, easily experience violence in the form of beatings or arguments by husbands or domestic perpetrators. Thus Rachel Vennya brings her YouTube content this time about women having their own perspective by being able to portray women as victims in the text, as well as women who represent the subject in news texts.